Permanent deformation analysis of base layers with recycled material: Effect of density and stress level. (March 2021) - Bilodeau, Jean-Pascal; Perez Gonzalez, Erdrick Leandro
Abstract: Full-depth reclamation techniques present numerous advantages for pavement rehabilitation strategies. The recycling process produces a thick layer of stabilized or unstabilized reclaimed materials, which is used as a new base layer of RAP aggregates. The compaction of the unstabilized thick layer is critical for adequate permanent deformation behaviour of the reclaimed layer. In some agencies, the smooth drum compaction is often used directly after the recycling process to compact the reclaimed materials. Previous studies demonstrated the challenges associated with adequate densification of the thick reclaimed layer through its whole thickness, leaving among other a material with a vertical density gradient. In that context, this study was designed to quantify the effect of the degree of compaction on the permanent deformation behaviour using cyclic triaxial tests. Granite and limestone aggregates were mixed with RAP in order to obtain mixes with 50% RAP, and each blend was tested using a permanent deformation test procedure at four different degree of compaction. One of the tested degree of compaction was a varying compacted density over the sample height. It was found that the analysis of this particular sample performance could be done on the basis of the average dry density of the sample. The shakedown ranges of each sample were analyzed with respect to stress ratio and degree of compaction. The behaviour for each type of mix was also similar. A generalized model was therefore proposed allowing to predict the range of permanent deformation behaviour knowing stress level and the degree of compaction. The general model between shakedown range and a relative stress ratio is based on a shift factor linking the effect of stress and density. Limit states were also defined for the possible ranges of behaviour with respect to the degree of compaction.